Las inversiones térmicas en la depresión de Sariñena - Martí Ezpeleta, Alberto (Geographicalia, 2017)
The topographic disposition of the Sariñena depression causes a high frecuency of thermic reversals that, sometimes, reach a high degree of intensity. This special behaviour affect on the thermic regime. the natural vegetation and the cultivations.